Pengaruh Lkpd Berbasis Creative Problem Solving (CPS) Terintegrasi Pembelajaran Berdiferensiasi Terhadap Kemampuan Berpikir Kreatif Peserta Didik Pada Pembelajaran IPAS Sekolah Dasar - Nofita Sari, Ema; Destini, Frida; Rohman, Fatkhur; Nurwahidin, Muhammad (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The problem in this research is the low creative thinking ability of students in science and science learning at SD Negeri 3 Sulusuban. The aim of this research is to determine the effect of Creative Problem Solving (CPS) based LKPD integrated with differentiated learning on elementary school IPAS learning. The method in this research is Quasi Experimental Group Design. The sample in the study was 42 people, the sample was determined using non-probability sampling techniques with a saturated sample type. Data collection uses test techniques, observation, documentation, interviews and questionnaires. Hypothesis testing uses a simple linear regression test. The results of the research show that there is an influence of LKPD based on Creative Problem Solving (CPS) integrated with differentiated learning on students' creative thinking abilities in class V IPAS learning at SD Negeri 3 Sulusuban for the 2024/2025 academic year.